Examining the Development of Sustainable Tourism on Phuket Island: A Literature Review with Implications for Tourism Planning - FUCHS, Kevin (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).26, 2022)
The conception of sustainable tourism is comparatively new and only started to emerge in the 1980s, whereas nowadays, it became a prevalent theme of discussion for researchers and tourism policymakers. Since then, sustainable tourism is often referred to as the holy grail and ultimate solution to achieve a balanced outcome that equally emphasizes environmental, economic, and socio-cultural aspects of tourism development. These factors are said to ensure active participation and assist in the process to create consensus amongst stakeholders. The tropical island of Phuket depends heavily on international tourism and generates most of its income from tourism receipts. Phuket developed quickly into a mass-tourism destination with its set of associated challenges derived from mass tourism. At present, the literature lacks a comprehensive account of perspectives from the tourism stakeholders, including indigenous people, local communities, visitors, industry, and government. Therefore, this review aims to serve as an insightful reference for policymakers and stakeholders that wish to affect change in the tourism industry for Thailand in general and Phuket specifically.